THE EFFECT OF BRAND TRUST AND UNIVERSITY REPUTATION ON STUDENT'S DECISION TO CHOOSE MANAGEMENT STUDY PROGRAM IN THE FACULTY OF ECONOMICS AND BUSINESS UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA - Arianty, Nel; Julita, Julita (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2021)
This study aims to determine the effect of brand trust and university reputation on purchasing decisions, namely student decisions in choosing the Management Study Program at the UMSU Faculty of Economics and Business. The approach taken in this research is to use an associative approach, namely research that seeks to examine how a variable has a relationship or relationship with other variables. Sampling was carried out by non-probability sampling technique, and by incidental sampling approach. The population in this study were all students of the 2018/2019 UMSU Management Study Program, and the sample used in this study amounted to 126 respondents using the slovin technique. Data were collected by questionnaire method. The data analysis technique used multiple linear regression, classical assumption test, t test, F test and coefficient of determination. The results showed that the brand trust variable had a significant effect on purchasing decisions, and the university reputation variable had a significant effect on purchasing decisions. Based on the simultaneous test, the variable brand trust and university reputation have a significant effect on purchasing decisions.